A comparison of Rv0559c and Rv0560c expression in drug-resistant Mycobacterium tuberculosis in response to first-line antituberculosis drugs. (January 2018) - Gamngoen, Ratikorn; Putim, Chanyanuch; Salee, Parichat; Phunpae, Ponrut; Butr-Indr, Bordin
Abstract: Drug resistance to Mycobacterium tuberculosis is a major health problem worldwide. Mycobacterium tuberculosis can progress to be mono-drug resistant or multi-drug resistant by improper treatment. The chemical stress of M. tuberculosis was performed in this study. Rv0559c is an unknown secreted protein. Rv0560c is a putative benzoquinone methyltransferase of M. tuberculosis cell. Rv0559c gene is located downstream of Rv0560c gene. Both genes respond to salicylate stress. Drug susceptible, isoniazid resistant, rifampicin resistant and multi-drug resistant phenotypes of M. tuberculosis clinical isolates were used to determine the expression of Rv0559c and Rv0560c by qRT-PCR. In all of mycobacteria strains there was up-regulation in both genes when stressed with isoniazid. This study determined the expression of both genes, which may play important roles in the drug resistance mechanism of mycobacteria.